Measurement and characterization of interfacial mechanical properties of graphene/MoS2 heterostructure by Raman and photoluminescence (PL) spectroscopy. (February 2022) - Du, Hongzhi; Kang, Yilan; Xu, Chaochen; Xue, Tao; Qiu, Wei; Xie, Haimei
Highlights: A synergistic measurement method, in which Raman and photoluminescence (PL) spectroscopy are employed to determine the strain fields of each layer, is proposed to measure the mechanical properties of the Graphene/MoS2 heterostructure. The strain distributions of each layer in the graphene/MoS2 double-layer heterostructure were quantitatively measured by the method. The interfacial mechanical properties and competition mechanism between the two interfaces (Graphene-MoS2 and MoS2 -substrate) are discussed. The differences in interfacial mechanical parameters between single-layer and double-layer structures, such as critical edge length and interface strength, were further discussed, which provides experimental bases for the practical application of nano-heterostructures. Abstract: The mechanical and physical properties of heterostructures formed by stacking different two-dimensional materials show great potential for the next generation of electronic/optoelectronic materials. Understanding the mechanical properties in the laminated structure is extremely significant in engineering. Aimed at the performance characterization of a vertical heterostructure, a synergistic experimental measurement method for the mechanical properties of graphene (Gr)/MoS2 heterostructures is proposed. First, Raman spectroscopy and photoluminescence (PL) spectroscopy are applied to calibrate and compare the coefficients of the peak shifts to the strain in the monolayer MoS2 . Then the strain-field information of MoS2 in the in-situ loading process of the substrate is measured, and the tangential interfacial stress distribution and evolution are analysed. Based on the calibration experiment, the strain fields of the two layers in the Gr/MoS2 heterostructure are measured, and the interfacial mechanical properties of the Gr-MoS2 and MoS2 -substrate interface are obtained. Finally, the difference of the mechanical parameters between MoS2 and the Gr/MoS2 on a flexible substrate are compared. This work provides a reference for the design and optimization of heterostructures in device engineering applications.